2004
DOI: 10.1021/tx049723c
|View full text |Cite
|
Sign up to set email alerts
|

Subway Particles Are More Genotoxic than Street Particles and Induce Oxidative Stress in Cultured Human Lung Cells

Abstract: Epidemiological studies have shown an association between airborne particles and a wide range of adverse health effects. The mechanisms behind these effects include oxidative stress and inflammation. Even though traffic gives rise to high levels of particles in the urban air, people are exposed to even higher levels in the subway. However, there is a lack of knowledge regarding how particles from different urban subenvironments differ in toxicity. The main aim of the present study was to compare the ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
193
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(207 citation statements)
references
References 29 publications
11
193
2
1
Order By: Relevance
“…Pulmonary inflammation and cardiovascular disease risk increased after air pollution control during the Olympic period (Huang et al, 2012a;Huang et al, 2012b). Moreover, enrichment of heavy metals, like Fe and others, in fine particles could also induce potential health consequences (Bachoual et al, 2007;Bigert et al, 2008;Karlsson et al, 2008;Karlsson et al, 2005;Morman and Plumlee, 2014). Considering the presence of PM sustained and accelerated by the strong air convection in the Beijing subway environment, there is immense scope for the collaboration between environmental and toxicological specialists.…”
Section: Implications For Subway Air Quality Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary inflammation and cardiovascular disease risk increased after air pollution control during the Olympic period (Huang et al, 2012a;Huang et al, 2012b). Moreover, enrichment of heavy metals, like Fe and others, in fine particles could also induce potential health consequences (Bachoual et al, 2007;Bigert et al, 2008;Karlsson et al, 2008;Karlsson et al, 2005;Morman and Plumlee, 2014). Considering the presence of PM sustained and accelerated by the strong air convection in the Beijing subway environment, there is immense scope for the collaboration between environmental and toxicological specialists.…”
Section: Implications For Subway Air Quality Managementmentioning
confidence: 99%
“…The secondary source is the particles carried by regular passengers and air flow from the outside urban environment (Kang et al, 2008;Li et al, 2006). Earlier toxicological research has pointed out that subway PMs induce oxidative stress in cultured human lung cell (Karlsson et al, 2005(Karlsson et al, , 2008 and impose strong self-limiting biological reactions on rodents (Bachoual et al, 2007), suggesting that the same PM might trigger health hazards in passengers. While lung cancer incidence was not increased , workers in the subway service were observed to suffer a long-term inflammatory process .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genotoxicity and oxidative stress effects of particles in the Stockholm subway have been compared with similar effects of aboveground particles by Karlsson et al (2005). They reported that the subway particles were eight times more genotoxic and four times more effective at causing oxidative stress than were aboveground particles.…”
Section: Adverse Health Effectsmentioning
confidence: 99%
“…Particularly, the composition of PM emitted from tunnels includes mainly iron compounds such as magnetite (Fe 3 O 4 ), hematite (Fe 2 O 3 ), and Fe metal (Jung et al, 2012;Mugica-Álvarez et al, 2012;Salma et al, 2007). With regard to the toxicity of those specific compounds, Karlsson et al (2005) reported that the subway particles were approximately eight times more genotoxic and four times more likely to cause oxidative stress in lung cells.…”
Section: Introductionmentioning
confidence: 99%